Cronologia vieţii literare româneşti. (VI) - Andrei Grigor; Nicoleta Ifrim; Cristina Balinte; Mihai Iovănel; Alina Crihană; Andrei Terian (Revista de Istorie și Teorie Literară)
This large piece of work represents a cronology of what happened Romanian publications in 1956, a black period where the litterature was under totalitarian commands and fear. This cronology was elaborated by a group of researchers such as Andrei Grigor, Nicoleta Ifrim, Cristina Balinte, Mihai Iovănel, Alina Crihană, Andrei Terian.